2022
DOI: 10.3389/fendo.2022.856973
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs Are Associated With Metabolic Markers in Adolescents With Hepatosteatosis

Abstract: BackgroundAltered hepatic microRNA (miRNA) expression may play a role in the development of insulin resistance (IR) and non-alcoholic fatty liver disease (NAFLD). Circulating miRNAs could mirror the liver metabolism.ObjectiveThis study aimed to assess the relationship between serum miRNA profile in children with obesity, IR, and NAFLD.MethodsAdolescents with obesity (n = 31) were stratified based on insulin resistance and NAFLD status. One-hundred seventy-nine miRNAs were determined in the serum by quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Correlation studies in all patients (n = 79) revealed that plasma hsa-miR-21-5p, expression level was positively correlated with serum insulin and the presence of insulin resistance and dyslipidemia (increased TC and TAG). Lin et al [ 34 ] suggested that altered plasma miRs might reflect liver lipid metabolism and said that hepatic miR expression contributes to the development of insulin resistance. This response is per both hsa-miR-21-5p and hsa-miR-155-5p would control the expression of genes involved in hepatic TAG and cholesterol metabolism, evidenced by silencing hepatic miR21 genes, where reduced hepatic inflammation and enhanced fibrosis were achieved [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Correlation studies in all patients (n = 79) revealed that plasma hsa-miR-21-5p, expression level was positively correlated with serum insulin and the presence of insulin resistance and dyslipidemia (increased TC and TAG). Lin et al [ 34 ] suggested that altered plasma miRs might reflect liver lipid metabolism and said that hepatic miR expression contributes to the development of insulin resistance. This response is per both hsa-miR-21-5p and hsa-miR-155-5p would control the expression of genes involved in hepatic TAG and cholesterol metabolism, evidenced by silencing hepatic miR21 genes, where reduced hepatic inflammation and enhanced fibrosis were achieved [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…We speculated that periodontitis might be affected by miR-125b-5p. Similarly, miR-17-5p and miR-21-5p were reported to play a part in periodontitis and migration of DCs and were predicted to get involved in NAFLD (Du et al, 2016;Kim et al, 2017;Reis et al, 2018;Cui et al, 2019;Zhang et al, 2020;Lin et al, 2022). Although these miRNAs have not been verified in the microenvironment of comorbidity with periodontitis and NAFLD, they also provide important therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…Correlation studies in all patients (n=79) revealed that plasma hsa-miR-21-5p expression level was positively correlated with serum insulin and the presence of insulin resistance, dyslipidemia (increased TC and TAG). Lin et al [26] suggested that altered plasma miRs might reflect liver lipid metabolism and stated that hepatic miRs expression contributes to the development of insulin resistance. This is per both hsa-miR-21-5p and hsa-miR-155-5p would control the expression of genes involved in hepatic TAG and cholesterol metabolism, evidenced by silencing hepatic MIR21 gene, where reduced hepatic inflammation and an enhanced fibrosis was achieved [27,28].…”
Section: Discussionmentioning
confidence: 99%